'CLUMSY AND ILLOGICAL'? RECONSIDERING THE WEST KIRBY HOGBACK. (2nd November 2016) - Williams, Howard
Abstract : This paper presents a fresh reading of a significant early medieval recumbent stone monument from West Kirby, Merseyside (formerly Cheshire). Rather than being a single-phased hogback, later subject to damage, it is argued that West Kirby 4 might have been carved in successive phases, possibly by different hands. It is suggested that the carvers had different abilities and/or adapted their work in response to the time pressures of a funeral or a shift in the location or function of the stone. While a single explanation for the character of the West Kirby monument remains elusive, the article proposes that, rather than 'clumsy and illogical', the stone was more likely a coherent but experimental, distinctive and asymmetrical, multi-phased and/or multi-authored creation. Through a review of the monument's historiography and a reappraisal of the details and parallels of its form, ornament and material composition, the paper reconsiders the commemorative significance of this recumbent stone monument for the locality, region and understanding of Viking Age sculpture across the British Isles. As a result, West Kirby's importance as an ecclesiastical locale in the Viking Age is reappraised.